(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
In this study, the clinical and laboratory characteristics of 158 children infected with hymenolepiasis, identified through epidemiological screening in 24 secondary schools in the Kasbi and Karshi districts of the Kashkadarya region, were investigated. The objective of the research is to analyze the clinical manifestations of parasitic invasion in the pediatric organism and to substantiate ways to increase treatment efficacy, taking into account immunological reactivity. The results showed that in 72% of children suffering from hymenolepiasis, the disease proceeds with clear clinical signs (dyspeptic, astheno-vegetative, and allergic syndromes). In laboratory analyses, persistent eosinophilia (46%) and hypochromic anemia (58%) were found to be dominant. The article analyzes the negative impact of the parasite on the immune system, especially the importance of restoring immune status in breaking the chain of repeated autoinvasion. At the conclusion of the study, an updated complex approach is proposed to increase treatment efficacy by enriching the traditional deworming course with immunomodulation and desensitization stages.